METHODOLOGY OF WORKING ON WORD GROUPS IN PRIMARY CLASSES - N.O. Khudoyberdiyeva; M.H. Ergashova (Journals Park Publishing, 2023)
This article describes the ideas and methods of teaching word groups in elementary grades. This article is relevant in that it focuses on the study of word groups, without giving theoretical information about the methods used.
Keywords: word groups, program, grammar, linguistic, vocabulary, situation, direction, spelling, method, technology, symbol, change.